(untitled) (International Journal of Architecture and Urbanism, 2020)
Hotel Resort and Cottage is a facility that will later help to develop culture, tourist attractions and also increase regional income. Until 2017 infrastructure development in Indonesia, in general, cannot be said to be equitable because so far, infrastructure development is only concentrated in Java and infrastructure development outside Java which, is less especially in remote areas and border areas. However, this issue canaddress by increasing Regional native revenue (PAD). Indonesia is known as a diverse country of natural and cultural resources, can be the main attraction in the tourism sector to bring domestic and foreign tourists to the area. The methodology applied from the design of this resort hotel and cottage is research directly to the location to see the soil conditions, contours, facilities around the area, wind direction, view, and sunlight. It is also a reference to some of the existing literature regarding resort hotels and cottages. The area selected for this project is Sipiso-Piso, Saribu Dolok Street, Merek District, Karo Regency because of the many resources that can manage optimally. This place has the potential to be used as a tourist attraction as well as a cultural development place. However, this place lacks facilities and infrastructure. After identifying the needs of generator activities, researchers make the design of Hotel Resort and Cottagein, addition to improving tourist sites and cultural education, this design also aims to increase the revenue of this area. Analysis and design concepts using the interpretation of Neo Vernacular Architecture